Study of the Electrochemical Behavior of Biodiesel Microemulsion - Moreira, Luiz Felipe Pompeu Prado [UNESP]; Beluomini, Maísa Azevedo [UNESP]; de Souza, João Carlos [UNESP]; Stradiotto, Nelson Ramos [UNESP] (My University, 2017)
Microemulsions have become a widely employed technique for the control of biodiesel quality but are still poorly understood as regard to their electrochemical behavior. In this work, we report the fundamental importance associated with the knowledge of electrochemical behavior of microemulsions composed of water in the presence of a supporting electrolyte, soybean biodiesel and propan-1-ol as consolute, along with the ferrocyanide–ferricyanide redox system applied as probe. The voltammetric results showed that for different compositions of microemulsions, variation in peak currents and change in system reversibility as well as in the electron transfer process were clearly noted. Furthermore, through the study of the diffusion coefficient, three different types of microemulsions including Oil/Water, Bicontinuous, and Water/Oil were successfully identified. Electrochemical impedance spectroscopy studies were also carried out aiming at obtaining more information regarding the electrode/solution interface. All the studies performed demonstrated that different types of microemulsions were formed upon exerting a direct influence on the electrochemical behavior of the redox probe. These results, in essence, point to the possibility of choosing a more suitable and advantageous microemulsion type for the development of an analytical method, as in the case, for example, of the microemulsions ME-2 and ME-3 which presented high voltammetric response in redox probe oxidation.
Keywords: Biodiesel Microemulsion; Chronoamperometry; Cyclic Voltammetry; Electrochemical Behavior; Electrochemical Impedance Spectroscopy